Effect of Bokashi on Growth of Oil Palm (Elaeis guineensis Jacq) Seedlings in Main Nursery in Different Soil Layer - Wiranda, Hasna Sahar; Syah, Ryan Firman; Rohmiyati, Sri Manu (Jurnal Biologi Tropis, 2025)
Limited fertile land encourages the use of subsoil for oil palm nurseries, despite its low organic matter content and dense structure. This study aims to examine the effect of bokashi varieties on the growth of oil palm seedlings in different soil layers. The study was conducted at KP2 Instiper Yogyakarta, Kalikuning Village, Maguwoharjo, Sleman, from January 15 to April 15, 2025 using a completely randomized design (CRD) with two factors, namely bokashi varieties (NPK control, sugarcane filter cake bokashi, water hyacinth, and LCC) and soil layers (topsoil and subsoil Regosol soil), with a mixing ratio of 1:1. Each treatment combination was repeated five times with a total of 40 seedlings. Data analysis was carried out through analysis of variance, followed by the DMRT test at a significance level of 5%. The results showed a significant interaction between bokashi varieties and soil layers on fresh and dry root weight, where all bokashi showed better results than the NPK control, with water hyacinth bokashi as the best. In conclusion, the use of bokashi, particularly from water hyacinth, can enhance the root growth of oil palm seedlings. These findings recommend the use of local organic materials as an alternative fertilizer for marginal subsoil.